A Century of Stability of Avannarleq and Kujalleq Glaciers, West Greenland, Explained Using High‐Resolution Airborne Gravity and Other Data. Issue 7 (5th April 2018) - An, L.; Rignot, E.; Mouginot, J.; Millan, R.
Abstract: The evolution of Greenland glaciers in a warming climate depends on their depth below sea level, flow speed, surface melt, and ocean‐induced undercutting at the calving front. We present an innovative mapping of bed topography in the frontal regions of Sermeq Avannarleq and Kujalleq, two major glaciers flowing into the ice‐choked Torssukatak Fjord, central west Greenland. The mapping combines a mass conservation algorithm inland, multibeam echo sounding data in the fjord, and high‐resolution airborne gravity data at the ice‐ocean transition where other approaches have traditionally failed. We obtain a reliable, precision (±40 m) solution for bed topography across the ice‐ocean boundary. The results reveal a 700 m deep fjord that abruptly ends on a 100–300 m deep sill along the calving fronts. The shallow sills explain the presence of stranded icebergs, the resilience of the glaciers to ocean‐induced undercutting by warm Atlantic water, and their remarkable stability over the past century. Key Points: We solve the topography of two major outlet glaciers in Central West Greenland to explain their exceptional stability in a warming climate We demonstrate the use of high‐resolution gravity to map bed topography where radar sounding and multibeam echo sounding techniques fail The multisensor/model approach solving of glacier mapping will enable ice sheet and ocean numerical model projection of sea level rise